2010
DOI: 10.1029/2009jb006651
|View full text |Cite
|
Sign up to set email alerts
|

Crustal thickness and average Vp/Vs ratio variations in southwest Yunnan, China, from teleseismic receiver functions

Abstract: [1] Recently, many portable broadband three-component seismic stations have been deployed in Yunnan, China. We use teleseismic receiver functions to determine the crustal thickness (H) and the crustal average compressional to shear wave velocity (V p /V s ) ratio (k) variations beneath in southwest Yunnan. By comparing the synthetics generated from dipping Moho models with those from a flat Moho model, it reveals that for the rays traveling along or around the updip direction, the differential arrival times of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
1
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 42 publications
0
21
1
1
Order By: Relevance
“…The Ailao Shan‐Red River fault zone is a tectonic boundary separating the Indochina block with an average crustal thickness of 36–37 km on the southwest and the Yangtze block with an average crustal thickness of 40–42 km on the northeast [ Sun et al , ]. The thickness of the crust beneath west Yunnan between the Ailao Shan‐Red River fault zone and the Nabang fault zone increases northward [ Sun et al , ; Wang et al , ]. The thickness of the lithosphere beneath west Yunnan [ Hu et al , ] is about 80–100 km, which is much thinner than that beneath Sichuan (140–180 km).…”
Section: Discussionmentioning
confidence: 99%
“…The Ailao Shan‐Red River fault zone is a tectonic boundary separating the Indochina block with an average crustal thickness of 36–37 km on the southwest and the Yangtze block with an average crustal thickness of 40–42 km on the northeast [ Sun et al , ]. The thickness of the crust beneath west Yunnan between the Ailao Shan‐Red River fault zone and the Nabang fault zone increases northward [ Sun et al , ; Wang et al , ]. The thickness of the lithosphere beneath west Yunnan [ Hu et al , ] is about 80–100 km, which is much thinner than that beneath Sichuan (140–180 km).…”
Section: Discussionmentioning
confidence: 99%
“…The inversion of teleseismic receiver functions is a strategy that is commonly employed to determine the velocity structure beneath three-component seismic stations, e.g., Langston (1977), Ammon and Zandt (1993), Searcy et al (1996), Midzi and Ottemoller (2001), Park et al (2009), Wang et al (2010). The receiver function technique exploits the fact that P-to-S converted waves have higher amplitudes in the radial component than in the vertical.…”
Section: Receiver Functionsmentioning
confidence: 99%
“…The PRF studies of Langston and Hammer [] revealed that the complex structures beneath sedimentary basins may induce strong P wave coda and interfere with the deconvolution. The strong multiples (especially PpPp ) generated by dipping interfaces would result in the failure of the deconvolution as well [ Wang et al ., ]. The Shanxi rift is covered by thick sediments, and the complex structures below cause the failure of calculating PRF (Figure b).…”
Section: Methods and Datamentioning
confidence: 99%